(untitled) (International Journal of Engineering Materials and Manufacture, 2021)
The continuous growth in the human population and climate change exacerbates the problems related to water scarcity. Harvesting the atmospheric water can mitigate the water scarcity in many regions around the globe. Fog collection using hybrid hydrophilic-superhydrophobic surfaces has the capacity to achieve a higher water collection rate. In this paper, a new method and materials are introduced to create the hybrid surfaces. The method includes additive manufacturing- to make sheets with holes-, mixing and casting polymeric matrix composite, and a controlled spray coating mechanism. The materials comprised of hydrophobic coating on top of the acrylic printed sheet and hydrophilic composite. The ratios of the pitches to diameters of the hydrophilic regions varied during the experiments to obtain the best water generation. The water collection rate for the sample with diameters of 583 um and a pitch of 1600 um has achieved 57% more than the untreated hydrophilic sample. The contrast in wettability accomplished by this novel method has the potential to be implemented on a large scale for atmospheric water harvesting.